Змістові особливості діяльності Європейської Асоціації Університетів - Ірина Чистякова (Pavlo Tychyna Uman State Pedagogical University, 2013)
У статті проаналізовано змістові особливості діяльності інноваційної освітньої мережі Європейська Асоціація Університетів; визначено поняття «інноваційні освітні мережі»; зазначено основні завдання діяльності Європейської Асоціації Університетів; схарактеризовано види діяльності досліджуваної мережі, зокрема, програми оцінки якості освіти; з'ясовано основні пріоритети Європейської Асоціації Університетів і всіх вищих навчальних закладів, що входять до її складу; представлено виміри міжнародних мереж у галузі вищої освіти. В статье проанализированы содержательные особенности деятельности инновационной образовательной сети Европейская Ассоциация Университетов; определено понятие инновационных образовательных сетей; представлены основные задания деятельности Европейской Ассоциации Университетов; дана характеристика видов деятельности исследуемой сети, а именно программы оценки качества образования; выяснены основные приоритеты Европейской Ассоциации Университетов и всех высших учебных заведений, которые входят в ее состав; представлены измерения международных сетей в сфере высшего образования. The European University Association (EUA) plays an important role in the future European higher education through research and unique knowledge in the education and diversity of the network. The activity of the EUA is characterized by providing equitable quality education in all educational institutions of the network and development of innovative practices. The content features of innovative education network the European University Association are analyzed in the article. The concepts of innovative educational networks are determined. The main tasks of the European University Association activity are submitted. Among them we single out: 1) organisation of European policy that strengthens the role of universities in the development of the knowledge society in Europe; 2) informing participants about the political developments and their impact on the higher education; 3) obtaining the universities of knowledge and experience in projects that underpin the policies of science; 4) strengthening the management, leadership and governance institutions through mutual learning, exchange and transfer of good practice; 5) strengthening the international position of undergraduate and magistrates in Europe and the training of scientific personnel by improving co-operation between members of the network and through dialogue with partner organizations in other regions of the world. The characteristic of different activities is presented, in particular the assessment of the quality of education, the main priorities of the European University Association and all higher institutions that make up its membership are founded. Measurements of international networks in the higher education are presented in the article. The European University Association is an important part of the educational community in Europe. The EUA membership is open to universities, associations and networks of higher education institutions. EUA builds strong universities in Europe through targeted measures to support their development. This includes political dialogues, conferences, seminars, projects and more targeted services such as institutional quality assessment program of education and work devoted to doctoral education. The author proves that the main priorities of the European University Association and all the universities that make up the network are the development of the European Higher Education Area; research and innovation; internationalization of higher education and research; improving the quality of European universities; governance, funding and autonomy.